2022
DOI: 10.1002/bbb.2409
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of anaerobic digested wastewater using magnetic nanoparticles and an external magnetic field for biogas enhancement

Abstract: Energy‐driven wastewater treatment plants (WWTP) have become an interesting research focus for environmental and process engineers. To meet the rigorous discharge limit standards imposed by the environmental protection agency (EPA) and South African national standards (SANS), the conventional treatment method has been improved and advanced technologies have been adapted. As such, studies on magnetized anaerobic digestion systems for wastewater treatment with the concept of energy generation have been explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The use of iron‐based NPs to boost methane and biogas generation, as reported by Liang et al ., 63 was observed. The MNPs addition had a good impact on methanations in addition to biogas production 24,65 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of iron‐based NPs to boost methane and biogas generation, as reported by Liang et al ., 63 was observed. The MNPs addition had a good impact on methanations in addition to biogas production 24,65 …”
Section: Resultsmentioning
confidence: 99%
“…After the 21 and 30 day incubation periods, the reactor efficiency was assessed by monitoring the contaminants removal using Equation (2). The analytical method used previously 24 was adopted in this study to determine the water quality.Removal efficiency0.25em)(%goodbreak=)(CiCfCigoodbreak×100…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Masood et al reported that applying a DMF inhibited the growth of Staphylococcus aureus and Pseudomonas aeruginosa . However, current studies mainly focused on the effects of static/constant magnetic fields on anaerobic systems. To our best knowledge, no reports have investigated the effects of DMFs on anaerobic digestion, especially on the individual stage of anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%